2022
DOI: 10.3390/bioengineering9080340
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteases from Adipose Tissue-Derived Stromal Cells Are Spatiotemporally Regulated by Hydrogel Mechanics in a 3D Microenvironment

Abstract: Adipose tissue-derived stromal cells (ASCs) are of interest in tissue engineering and regenerative medicine (TERM) due to their easy acquisition, multipotency, and secretion of a host of factors that promote regeneration. Retention of ASCs in or around lesions is poor following direct administration. Therefore, for TERM applications, ASCs can be ‘immobilized’ via their incorporation into hydrogels such as gelatine methacryloyl (GelMA). Tweaking GelMA concentration is a common approach to approximate the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 69 publications
(83 reference statements)
1
15
0
Order By: Relevance
“…As stated above, the observed vascularization was accompanied by the extensive remodeling of ECM. This corroborates our earlier observations that mesenchymal cells embedded in collagen-mimicking hydrogels respond to the matrix by remodeling it [ 21 , 22 ].…”
Section: Resultssupporting
confidence: 92%
“…As stated above, the observed vascularization was accompanied by the extensive remodeling of ECM. This corroborates our earlier observations that mesenchymal cells embedded in collagen-mimicking hydrogels respond to the matrix by remodeling it [ 21 , 22 ].…”
Section: Resultssupporting
confidence: 92%
“…To illustrate, we have shown that ASCs respond to pathological stiffnesses with apoptosis while they thrive in softer matrices [ 49 ]. In fact, ASCs secrete MMPs that degrade the matrix in a stiffness-dependent fashion [ 50 ]. Thus, ECM fulfills a rather strong instructive function, including direct regulation of relevant physiological processes [ 51 ].…”
Section: The Extracellular Matrix As An Instructive Scaffold and Deli...mentioning
confidence: 99%
“…The TGF-1 implanted in nano-spheres can maintain a sustained release for up to 21 days and enhance the encapsulated MSCs’ chondrogenic development. As a result, such materials exhibit high potentials in cartilage-regeneration applications [ 55 , 56 ].…”
Section: 3d Bioprinting Techniquesmentioning
confidence: 99%